Some Aspects of Girth Increment in Khaya grandifoliola C. DC. ( Meliaceae ) - Ola-Adams, B. A.; Charter, J. R. (Indian Forester, 1980)
The effects of temperature, relative humidity, rainfall and sunshine hours on girth growth of Khaya grandifoliola were studied in this paper. Girth growth was most active during March-July. There were significant positive correlations between rainfall, temperature and girth growth while correlation between girth growth and sunshine hours was significantly negative. Leaf flush occurs between December and January and flowering occurs between late December to February.